THE INFLUENCE OF AUDITOR INDEPENDENCE, COMPETENCE AND ETHICS ON AUDIT QUALITY WITH AUDIT FEES AS A MODERATION VARIABLE - Farhan Ramadhan; Agus Ismaya H.; Denny Susanto (ZILLZELL MEDIA PRIMA, 2025)
This study aims to analyze the influence of auditor independence, competence, and ethics on audit quality with audit fees as a moderation variable. This study uses a quantitative approach with a data collection method through questionnaires distributed to Public Accounting Firms in DKI Jakarta Province. The purposive sampling technique is used in the selection of respondents to ensure the relevance and quality of the data obtained. Data analysis was carried out using descriptive statistical methods and Structural Equation Modelling (SEM) through Partial Least Square (PLS). Descriptive statistics provide an overview of the characteristics of respondents, while PLS is used to assess the outer model and the inner model. The results of the study show that the independence, competence, and ethics of auditors have a positive and significant influence on audit quality. In addition, audit fees have been proven to moderate the relationship between independence, competence, and ethics of auditors to audit quality. These findings emphasize the importance of independence and ethics in improving the quality of the audits produced.